PERANCANGAN PETA WISATA GRAND MAERAKACA SEBAGAI PENGEMBANGAN IDENTITAS PARIWISATA - Farhania Apriliyani; Suci Salsabila; Abi Senoprabowo; Mohamad Taufik (AKSA: Jurnal Desain Komunikasi Visual, 2021)
A map provides a corporate identity as a medium of information as well as a clear position on the tourist destination, thus making it easier for visitors to visit. Grand maerakaca design travel maps using the glass box method. The grand maerakaca isa cultural educational field. Grand maerakaca's grand maerakaca tourist map was prepared through preparation, incubation, ironing, and verification, which produced simple, modern design but did not eliminate the original element.